Collaborative Governance of the Tourism Potential Development in Merauke District - Edoardus E. Maturbongs; Ransta L. Lekatompessy (Jurnal Ilmu Sosial dan Humaniora, 2025)
The development of tourism potential plays a crucial role in driving community economic growth while simultaneously serving as a means of preserving tourist attractions in accordance with local environmental conditions. This study focuses on policy formulation aimed at designing a collaborative governance model for tourism potential development in Merauke Regency. The research employs a qualitative approach, utilizing field observations, in-depth interviews, Focus Group Discussions (FGDs), and document studies to collect data. Data analysis follows a descriptive qualitative method based on the Miles and Huberman framework, which includes data reduction, data presentation, and conclusion drawing and verification to interpret the data and formulate  policy recommendations. The findings indicate that a collaborative model for tourism policy development in Merauke Regency effectively integrates Thomas R. Dye’s group formulation theory with the Pentahelix framework within Collaborative Governance. The five Pentahelix elements-government, business actors, academics, community, and media-function as active stakeholders in the formulation and implementation of policies. The resulting policies are participatory, equitable, and sustainable, characterized by a holistic and locally contextualized approach that maintains ecological, social, and economic balance, as well as transparency and accountability. This model effectively addresses the needs for inclusive tourism development oriented towards community welfare. Academically, this study contributes significantly to the advancement of collaborative governance theory in the tourism sector. Practically, its findings serve as a valuable guideline for stakeholders in designing and implementing sustainable, community-oriented tourism policies.